Leven Thumps and the Gateway to Foo - Skye, Obert; Sowards, Ben ([Salt Lake City, UT] : Shadow Mountain, 2005)
When fate brings fourteen-year-old Leven and thirteen-year-old Winter together, they discover that for mankind to continue dreaming, the gateway between reality and dreams needs to be found and demolished.
aSeries book number from spine.
aSequel: Leven Thumps and the whispered secret.
Keywords: Magic -- Fiction; Dreams -- Fiction; Fiction